ALAM DAN KESEHATAN MENTAL - Febrita, suci Shawmy; desmita, desmita (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
Mental health is an important aspect of human well-being in living life, but is often neglected. Inhuman life, of course, there is pressure (stress) for humans to move, good stress is certainly useful forhuman survival. If bad or excessive stress causes people to experience mental health disorders suchas anxiety and depression. The era of technological and scientific development not only helps makehuman tasks easier but also increasingly separates humans from nature. The relationship betweenhumans and nature is harmonious, nature provides every need for human life and nature needs to beprotected and cared for by humans to create a good ecosystem. If there is no connection orconnectivity between humans and nature, it will certainly cause humans to experience bad stress andeven physical and psychological illnesses. Humans use various methods to reduce stress bothpharmacologically and non-pharmacologically. Natural therapy is a non-pharmacological oralternative way to reduce stress. Nature can have a positive effect on human mental health. Theresearch method used is a literature study, where the data sources come from books, articles,journals, research reports, and electronic media. The results of this research are that nature therapycan help human mental health with various activities that can be done in nature, such as walking inthe forest slowly without sound, inhaling the aroma of the forest, shouting activities, observinganimals around, meditation activities, soaking in the water. river, activities to hear the sound ofwater, water stone therapy activities, tea-drinking activities, tree-hugging activities, and art therapy(drawing or painting). These activities can help increase positive thoughts, self-acceptance, feelingsof health, calm, joy, and prosperity and reduce levels of stress anxiety, and other mental pressure